Akademiko Konstantino Jablonskio asmeninė biblioteka: bibliofilijos aspiracijos - Narbutienė, Daiva (Knygotyra, 2003)
The library of the Lithuanian Academy of sciences got the collection of books by academician Konstantinas Jablonskis at 1964. Richness and plenty charakterized this collection: it was an all-purpose scientific library by a real bibliophile. There are the books and the periodicals from the fields of history, law, philology and the natural history. It comprises now the memorial collection of K. Jablonskis of more than 9000 items of different publications. The present article discusses the rara of this collection in three aspects. The first one involves the bibliographical rarities and the unique copies; the second one - the copies with the autograhs by different authors or well-known persons; the third one - the copies with the inscriptions by the previous owners. The factors presenting the bibliophilistic aspirations of K. Jablonskis are discussing in this article too.